The comparison of hospitals’ performance indicators before and after the Iran's hospital care transformations plan - Sajadi, Haniye Sadat (J Educ Health Promot, 2017)
INTRODUCTION: Hospital care transformation plan (HCTP) was implemented, in 2014, with the aim of ensuring all Iranians have fair access to hospital care, mainly in the public sector. It was assumed that HCTP would lead to increased quality and effectiveness of health care in public hospitals. To explore whether HCTP has achieved its aim, this study has investigated the impact of this plan on performance indicators (PIs) of the public hospitals. MATERIALS AND METHODS: This cross-sectional descriptive study was conducted in 2016. The study population included all hospitals in the Isfahan City. Data (10 selected PIs) were collected through formal reports which were available at the Isfahan University of Medical Sciences and analyzed using Statistical Package for Social Sciences (version 17). The statistical significant level analysis was 0.05. RESULTS: After HCTP, it was shown an increase of (1) Bed occupancy, bed turnover, occupied bed-days, inpatients visits, and number of surgeries in all types of hospitals, (2) Outpatients’ visits in all hospitals except private ones, (3) Emergency visits in public and social security hospitals, and (4) Natural deliveries in public and semi-public hospitals. Furthermore, the average length of stay and hospital mortality rate has decreased in all types of hospitals after HCTP implementation. DISCUSSION AND CONCLUSION: Although, improving PIs of hospitals were not directly stated and known objectives of HCTP implementation, it seems HCTP could improve the performance of all hospitals, including involved and noninvolved ones.